1993
DOI: 10.1063/1.464164
|View full text |Cite
|
Sign up to set email alerts
|

Grafted polymer layers under shear: A Monte Carlo simulation

Abstract: Endgrafted polymers at surfaces exposed to a shear flow are modeled by a nonequilibrium Monte Carlo method where the jump rate of effective monomers to neighboring lattice sites against the flow direction is smaller than in the flow direction, assuming that this difference in jump rates is proportional to the local velocity of the flowing fluid. In the dilute case of isolated chains, the velocity profile is assumed linearly increasing with the distance from the surface, while for the case of polymer brushes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 116 publications
(115 citation statements)
references
References 37 publications
9
106
0
Order By: Relevance
“…Brushes at smaller areal fractions deform at a smaller value of Wi due to the increased penetration of the velocity into the brush. Many of these trends had been witnessed in previous simulations, 16,[31][32][33][34][35][36][37][38] but in addition we derived scalings for brush rheology observed in the simulations and compared steady to oscillatory shear. As in previous simulations, 16,31-37 we found no brush thickening under steady shearing which contrasts with many theoretical studies.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Brushes at smaller areal fractions deform at a smaller value of Wi due to the increased penetration of the velocity into the brush. Many of these trends had been witnessed in previous simulations, 16,[31][32][33][34][35][36][37][38] but in addition we derived scalings for brush rheology observed in the simulations and compared steady to oscillatory shear. As in previous simulations, 16,31-37 we found no brush thickening under steady shearing which contrasts with many theoretical studies.…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33][34]37,38 Monte Carlo simulations by Lai and Binder 31 and Miao et al 33 for weak flows covering a decade of shear rates found no appreciable change in brush height. Lai and Lai 32 simulated larger shear rates (about 6 times the largest shear rate in Lai and Binder's simulations) and found no appreciable change in the brush thickness.…”
Section: Equilibrium Chain Dimensionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The brush structure and its properties can be controlled by tuning the grafting density, and variation of polymer molecular weight, temperature, and solvent quality [18]. Numerous theoretical [19][20][21][22][23][24][25][26], experimental [27][28][29][30][31], and simulational [32][33][34][35][36][37][38][39][40][41][42][43][44][45] studies have examined the structure and properties of polymer brushes. There exist, however, sometimes significant differences between the theoretical and the experimental investigations of polymer brushes.…”
Section: Introductionmentioning
confidence: 99%